2018
DOI: 10.31390/taboo.17.4.06
|View full text |Cite
|
Sign up to set email alerts
|

A Student Saved is NOT a Dollar Earned: A Meta-Analysis of School Disparities in Discipline Practice Toward Black Children

Abstract: Exclusionary school discipline practices continue to play a key explanatory role in racially disproportionate outcomes in the justice system. Three decades of research substantiate the disproportionality of discipline practices and the negative effects on Black students. However, a meta-analysis of this phenomenon and its moderators remains absent but is warranted based on its practical and empirical import. Thus, this meta-analysis synthesized the research on school discipline disproportionality between Black… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Not only are people of color overrepresented in the criminal justice system (Carson 2020; U.S. Office of Justice Programs 2021), but Black and-to a lesser extent-Latinx students disproportionately experience suspension and expulsion compared to White students (U.S. Department of Education 2019). Multivariate analyses of the characteristics and conditions associated with exclusionary school punishment corroborate that minority students are likelier to be disciplined net of other influences (e.g., Anyon et al 2014;Gregory and Weinstein 2008;Ksinan et al 2019;Lehmann and Meldrum 2021;Mittleman 2018;Mowen and Brent 2016;Peguero and Shekarkhar 2011;Rocque and Paternoster 2011;Skiba et al 2011;2014;Young, Young, and Butler 2018). Corporal punishment also has been used more frequently for students of color (McClure and May 2014), and minority youth are less likely than their White peers to receive restorative disciplinary outcomes such as conferencing, mediation circles, and restitution (Ramey 2016;Skiba et al 2016;Skiba and Rausch 2006).…”
Section: The School-to-prison Pipelinementioning
confidence: 88%
“…Not only are people of color overrepresented in the criminal justice system (Carson 2020; U.S. Office of Justice Programs 2021), but Black and-to a lesser extent-Latinx students disproportionately experience suspension and expulsion compared to White students (U.S. Department of Education 2019). Multivariate analyses of the characteristics and conditions associated with exclusionary school punishment corroborate that minority students are likelier to be disciplined net of other influences (e.g., Anyon et al 2014;Gregory and Weinstein 2008;Ksinan et al 2019;Lehmann and Meldrum 2021;Mittleman 2018;Mowen and Brent 2016;Peguero and Shekarkhar 2011;Rocque and Paternoster 2011;Skiba et al 2011;2014;Young, Young, and Butler 2018). Corporal punishment also has been used more frequently for students of color (McClure and May 2014), and minority youth are less likely than their White peers to receive restorative disciplinary outcomes such as conferencing, mediation circles, and restitution (Ramey 2016;Skiba et al 2016;Skiba and Rausch 2006).…”
Section: The School-to-prison Pipelinementioning
confidence: 88%
“…For example, nationally, suspension rates are among the highest for both Black boys and girls (Epstein, Black, & Gonzalez, 2017;Onyeka-Crawford et al, 2017;Schott Foundation, 2010;Skiba, Michael, Nardo, & Peterson, 2002). A meta-analysis by Young and Butler (2018) exploring school disparities in discipline practices found that the odds of Black students being disciplined were 2.5 times higher than White students. Notably, rates of disproportionate discipline action did not significantly differ among Black boys and girls compared with White students (Young & Butler, 2018).…”
Section: A Gendered Lens On Black Adolescents' School Experiencesmentioning
confidence: 99%
“…A meta-analysis by Young and Butler (2018) exploring school disparities in discipline practices found that the odds of Black students being disciplined were 2.5 times higher than White students. Notably, rates of disproportionate discipline action did not significantly differ among Black boys and girls compared with White students (Young & Butler, 2018). However, much of school discipline literature has focused on Black boys (Bryan, 2020).…”
Section: A Gendered Lens On Black Adolescents' School Experiencesmentioning
confidence: 99%
See 2 more Smart Citations